2020
DOI: 10.5296/jfs.v9i1.17045
|View full text |Cite
|
Sign up to set email alerts
|

Following a Low Carbohydrate, High Fat Diet Compared to Reduced Calorie, High Carbohydrate Diet as a Nutritional Intervention in Type Two Diabetes Mellitus Patients: A Systematic Review

Abstract: There is evidence supporting individuals with type 2 diabetes benefit from lifestyle changes through a nutrition intervention that improves diabetic (blood glucose and HgbA1c) and cardiovascular (total cholesterol, HDL, LDL, and triglycerides) biomarkers. The objective of this systematic review was to evaluate if patients with type 2 diabetes following a low carbohydrate, high fat eating pattern is more effective than following a reduced caloric, high carbohydrate eating pattern in the improvement of diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In general behavioural terms and specifically in dietary modification, the more restriction the likelihood of long‐term adherence is lower 49,50 . Therefore, while the studies reported in this and other meta‐analyses 26,51 broadly show greater improvements in glycaemic control and sometimes weight and lipids with VLC/KDs, studies are generally limited to 6 or 12 months, dropout rates in the ketogenic group can be as high as 54%, 32 and reported carbohydrate intake is often greater than what would constitute a KD by the end of the study (Table 1). Dansinger et al have previously shown that weight loss is more related to adherence to a diet than to the actual dietary composition, and in their 12‐month study the VLC/KD had the lowest adherence 52 …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In general behavioural terms and specifically in dietary modification, the more restriction the likelihood of long‐term adherence is lower 49,50 . Therefore, while the studies reported in this and other meta‐analyses 26,51 broadly show greater improvements in glycaemic control and sometimes weight and lipids with VLC/KDs, studies are generally limited to 6 or 12 months, dropout rates in the ketogenic group can be as high as 54%, 32 and reported carbohydrate intake is often greater than what would constitute a KD by the end of the study (Table 1). Dansinger et al have previously shown that weight loss is more related to adherence to a diet than to the actual dietary composition, and in their 12‐month study the VLC/KD had the lowest adherence 52 …”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the value of VLC/KD for weight loss, glycaemic control and CVD risk in these groups is uncertain. 13,14,25,26 This study aimed to estimate the effect of VLC/KD compared with diets higher in carbohydrate, assessed by meta-analysis of randomized controlled trials (RCTs) in people with pre-diabetes or T2D, on glycated haemoglobin (HbA1c) and related metabolic variables.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of low-carbohydrate diets in the management of glycemia has been extensively studied; however, findings have been inconclusive. Some studies asserted the superiority of low carbohydrate diets in glycemic control compared to other diets (usually low-fat diets), suggesting a dose-dependent relationship whereby a greater carbohydrate restriction results in better glycemic control, while others warned against the unsustainability of this approach’s effects or indicated no advantage at all [ 89 , 101 , 102 , 103 , 104 , 105 ]. Moreover, depending on the choice of foods that replace carbohydrates, low carbohydrate diets may be associated with adverse metabolic outcomes and micronutrient deficiencies [ 106 ].…”
Section: Dietary Management Of Diabetesmentioning
confidence: 99%